2013
DOI: 10.1007/s00484-013-0770-8
|View full text |Cite
|
Sign up to set email alerts
|

Climate factors affecting fertility after cervical insemination during the first months of the breeding season in Rasa Aragonesa ewes

Abstract: This study was carried out to examine the impact of several climate variables on the pregnancy rate after cervical artificial insemination (AI) of Rasa Aragonesa ewes. Data were derived from 8,977 inseminations in 76 well-managed flocks performed during the first month of the breeding season (July to October). The following data were recorded for each animal: farm, year, month of AI, parity, lambing-treatment interval, inseminating ram, AI technician, and climatic variables such as mean, maximum and minimum te… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
16
0
3

Year Published

2016
2016
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 23 publications
(22 citation statements)
references
References 19 publications
3
16
0
3
Order By: Relevance
“…Few studies have examined the effects of meteorological factors on the success of AI in small ruminants. In sheep, in the first month of the breeding season, maximum temperature before AI and pregnancy rate are negatively correlated (Santolaria et al 2014). Our research has shown that meteorological factors had a significant effect on the pregnancy rate after AI in sheep, which occurred in a season-dependent manner; e.g., the effects of temperature are reversed between the hot and cold seasons .…”
Section: Introductionmentioning
confidence: 81%
“…Few studies have examined the effects of meteorological factors on the success of AI in small ruminants. In sheep, in the first month of the breeding season, maximum temperature before AI and pregnancy rate are negatively correlated (Santolaria et al 2014). Our research has shown that meteorological factors had a significant effect on the pregnancy rate after AI in sheep, which occurred in a season-dependent manner; e.g., the effects of temperature are reversed between the hot and cold seasons .…”
Section: Introductionmentioning
confidence: 81%
“…Respecto al ITH (calculado empleando la fórmula de Thom [22]), que indica el estrés térmico del animal causado por los efectos combinados de la temperatura y la humedad del aire, también se observaron diferencias significativas entre sistemas de manejo. No obstante, conforme a los rangos propuestos por Santolaria, et al [13] para ovejas de raza aragonesa, los valores obtenidos (en el rango 61,6-63,2) fueron inferiores a 72 en todos los casos, excluyendo así la existencia de estrés térmico para los corderos.…”
Section: Efecto Del Manejo Sobre Las Condiciones Ambientalesunclassified
“…Con respecto a la humedad relativa (HR), en ocasiones se valora junto con la temperatura en un único parámetro, el denominado índice de temperatura-humedad (ITH), que mide el confort térmico y evalúa el riesgo de estrés por calor sobre la producción y la mortalidad. Se recomiendan valores de humedad relativa del 65-75% [8] y de ITH<72 [13]. En un ensayo de Bello, et al [14], en que se analizó la relación entre parámetros ambientales y la mortalidad de corderos en un cebadero comercial, se observó que en invierno, la humedad fue el parámetro ambiental más correlacionado con la mortalidad, mientras que en verano la mortalidad estuvo relacionada con la temperatura, el punto de rocío y ITH.…”
Section: Introductionunclassified
“…Fertilidad (%) (corderos/ oveja inseminada) Prolificidad (corderos/ parto) dos por Santolaria et al (2014) quienes detectaron un descenso de probabilidad de gestación por encima de los 30 ºC en Rasa aragonesa. Palacios y Abecia (2015) detectaron también que los factores metorológicos afectaban a la fertilidad tras la IA, de forma que las temperaturas no extremas la favorecían.…”
Section: Fecundidad Factorunclassified